Nutrients utilization, methane emission, immune function, blood metabolites and performance of buffalo calves fed Trachyspermum copticum seed oil - PAWAR, M M; KAMRA, D N; CHAUDHARY, L C; AGARWAL, N; CHATURVEDI, V B (The Indian Journal of Animal Sciences, 2019)
The effect of ajwain seed oil (Trachyspermum copticum, AjO) on nutrient digestibility, methane emission, immune status, blood metabolites and growth performance was studied on 15 growing male buffalo calves. The animals were divided into three groups in completely randomized design and assigned to three dietary treatments, viz. control without additive (T1), AjO at the rate of 1 ml/calf/day (T2) and AjO at the rate of 2 ml/calf/day (T3). Feeding was continued for 120 days. The dry matter intake (kg/d) was higher by 3 and 8% and average daily weight gain by 10 and 16% in T2 and T3 groups as compared to control (T1) group, but differences were not significant. There was no effect on apparent digestibility of dry matter, organic matter, ether extract, neutral detergent fibre and acid detergent fibre except crude protein digestibility which was higher in T3 group as compared to control. The methane production and energy metabolism were not changed by feeding of AjO. The animals of T3 group were in higher nitrogen balance accompanied with low blood urea level. The blood metabolites and immune status (cell mediated and humoral immune response) reflecting health of the animals, were similar and within normal range in all the groups. Though AjO feeding could not affect the overall performance of the animals but was able to modulate protein etabolism resulting in improvement in protein utilization efficiency.